Smart railway sleepers - a review of recent developments, challenges, and future prospects. (15th February 2021) - Jing, Guoqing; Siahkouhi, Mohammad; Riley Edwards, J.; Dersch, Marcus S.; Hoult, N.A.
Highlights: A comprehensive literature review of the development and use of smart sleepers. Detailed categorization of sensing types and applications related to smart sleepers. Discussion of concrete sleeper load bearing measurement systems. Analysis of the path forward for increased adoption in light of current limitations. Abstract: To date, the application of self-sensing or other structural health monitoring (SHM) technologies in railway sleepers is limited. Development and deployment of smart sleepers can provide value to rail infrastructure owners and maintainers by informing maintenance and replacement decisions, collecting support condition data providing insight into the health of the track substructure, supporting numerical model development and validation, and providing energy harvesting capabilities. These result in extending the service life of sleepers and the surrounding railway infrastructure providing a key element of sustainable design for the track systems. This paper provides a comprehensive review of recent smart sleeper developments and describes challenges to more widespread adoption. Limitations to using smart sleepers include their production cost and limited data on long term performance, which can be incompatible with the sleeper's service life. Potential solutions for overcoming the challenges associated with the application of smart sleeper technologies include the use of intrinsic self-sensing concrete, adding self-healing features, taking advantage of recent wireless sensing developments, and connecting with the emerging use of Internet of Things (IoT) technology. Opportunities abound to expand smart sleeper deployment for condition monitoring and real-time management of track assets, to decrease the life cycle cost (LCC) of track components and increase infrastructure availability whereby increasing track capacity.